‘So far and yet so near’: Cuba and revolutionary Burkina Faso - Pritchard, Liam (2025)
In August 1983, a group of radical junior officers and civilian revolutionaries seized power in Upper Volta. Led by Captain Thomas Sankara, who would become widely known as ‘Africa’s Che Guevara’, Burkina Faso – as the country was renamed – embarked upon a path of radical change, breaking from its neocolonial past. Radical nationalist and anti-imperialist in their ideological outlook, the Burkinabè revolutionaries appeared deeply inspired by the example of the Cuban Revolution. Over the course of the short-lived Burkinabè Revolution (1983-1987) they adopted the Cuban national motto, implemented similar mass political organisations, and seemingly endeavoured to match the most notable social achievements of that distant Revolution. Yet, how is this apparent influence of Cuba to be understood? Rather than ‘soft power’, and the direct product of policy from Havana, that influence took hold organically and clearly possessed a counter-hegemonic quality. An original neo-Gramscian approach to understanding Cuba’s influence, and reconceptualising the nation’s foreign relations more broadly, permits us a truer picture of its character: functioning to subvert the coercive and consensual elements of hegemonic world order. The Burkina case is particularly revealing in understanding this influence, as well as being one of many internationalist missions hitherto neglected by the existing literature, with its continuing focus on Cuba’s involvement in Angola. Havana’s assistance to revolutionary Burkina in healthcare, education, and security matters – among other areas – is instructive of Cuba’s many small internationalist missions on the continent, and of the counter-hegemonic character of its foreign relations.